2015
DOI: 10.1007/s00223-015-9969-5
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-1 and Sclerostin Serum Levels in Patients with Systemic Mastocytosis

Abstract: Bone involvement, mainly osteoporosis but also osteosclerosis, is frequent in patients with indolent systemic mastocytosis (ISM). The recent characterization of the canonical Wnt/β-catenin pathway in the regulation of bone remodeling provided important insights for our understanding of the pathophysiology of a number of conditions. The regulation of Wnt pathway in bone is predominantly driven by the production of receptor inhibitors such as Dickkopf-1 (DKK1) and sclerostin (SOST). This study aimed to explore i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The relationship between DKK1 and OPG has also been demonstrated in OB precursors [14]. In agreement with our findings, it was demonstrated that high DKK1 serum levels correlate with CTX amounts in multiple myeloma, in chronic glucocorticoid treatment [22,30], in mastocytosis [31] and in rheumatoid arthritis [32]. In patients with OI bone turnover is generally increased but an increase also in RANKL/OPG ratio and its positive correlation with DKK1 could confirm in vivo the prevalence of bone resorption showed in vitro and the possible role of DKK1.…”
Section: Discussionsupporting
confidence: 91%
“…The relationship between DKK1 and OPG has also been demonstrated in OB precursors [14]. In agreement with our findings, it was demonstrated that high DKK1 serum levels correlate with CTX amounts in multiple myeloma, in chronic glucocorticoid treatment [22,30], in mastocytosis [31] and in rheumatoid arthritis [32]. In patients with OI bone turnover is generally increased but an increase also in RANKL/OPG ratio and its positive correlation with DKK1 could confirm in vivo the prevalence of bone resorption showed in vitro and the possible role of DKK1.…”
Section: Discussionsupporting
confidence: 91%
“…Confirming this, bone formation and resorption markers were found to be increased in SM patients (153). However, other authors reported increased serum levels of dickkopf 1 and sclerostin, both inhibitors of the osteoanabolic Wnt signaling pathway, indicating reduced bone formation (154,155). IL-6 levels are also increased in SM, and correlate with the severity of the symptoms and bone loss (155,156).…”
Section: The Role Of Mast Cells In Bone Disorders Osteoporosismentioning
confidence: 72%
“…The PTH analogue teriparatide may promote further proliferation of mast cells and has not been recommended in this setting ( 9 ). Dickkopf-1 (DKK1) and sclerostin, receptor inhibitors of the Wnt pathway, have been studied in patients with SM, with DKK1 levels appearing to be elevated in comparison to controls but not sclerostin ( 17 ). It is thus unclear whether the Wnt/β-catenin pathway plays a significant role in the pathophysiology of SM.…”
Section: Treatment Of Osteoporosis In Systemic Mastocytosismentioning
confidence: 99%